The influence of the summer sea breeze on thermal comfort in Funchal (Madeira): a contribution to tourism and urban planning - Lopes, António (2019)
Tourism plays a crucial role for the development of coastal areas. Despite the mildness of Madeira’s climate, very hot days can occur during summer, a situation to which most tourists from northern Europe (the majority of foreign tourists) are poorly adapted. As sea breezes strongly contribute to moderate heat stress in urban environments, their influence on the thermal comfort on the island has been studied. Sea breezes occurred on 84 % of the days during the period under study (May to October 2006). They usually start around 09:30 h and end after 22:00 h, with an average duration of about 12:50 hours and a mean velocity of 2.9 m/s. Physiologically Equivalent Temperature (PET) was used to evaluate the thermal comfort of a sample of days during the summer of 2006. It was concluded that most of the sites in the city are “slightly comfortable” during normal days with sea breeze, but only shore sites and the highest green areas offer some comfort during hot days. Inside the city, the thermal perception is generally “hot” and strong heat stress can occur. As sea breezes are important to mitigate heat stress, some basic guidelines were presented: urban planners should take advantage of this wind system avoiding dense construction near the shoreline that would act as a barrier to the renewal of the air inside the city. In terms of tourism, planners and local authorities should provide solutions to mitigate the negative effects during hot periods, creating a system to warn and relocate more vulnerable tourists to places near the shore line, to the mountains, to gardens and air-conditioned buildings. In combination with other components (beauty of the island, gastronomy, cultural values and safety), climate information can be a factor of attractiveness to tourists.